Carte particuliére de l'Amerique Septentrionale : ou sont compris le destroit de Davids, le destroit de Hudson, &c - Mortier, Pieter (Chez Pierre Mortier, 1693)
Map shows Iceland, Greenland, and the North Atlantic coast of North America including "Baffins Bay" and Hudson Bay. Relief shown pictorially. Scale not given.